ANALISIS RETURN ON INVESTMENT (ROI) DAN RESIDUAL INCOME (RI) GUNA MENILAI KINERJA KEUANGAN PERUSAHAAN: Studi pada PT Industri Jamu dan Farmasi Sido Muncul, Tbk yang Terdaftar di BEI - Hamidah, Nurul; Prabowo, Heri; Setiawati, Ira (Jurnal Ilmiah Ekonomi, Manajemen dan Syariah, 2023)
This research is motivated by the company's goals that are to generate profits, maximize firm value, and minimize costs. To find out whether or not the company's goals are achieved, it is necessary to know the financial performance of the company. This study uses an investment center assessment based on Return On Investment and Residual income. The type of research used is the descriptive quantitative approach and the sampling technique used is purposive sampling. The object of the research is PT Industri Jamu and Pharmacy Sido Muncul, Tbk which is listed on the IDX for the 2016-2020 period. The data used is secondary data obtained from the Indonesia Stock Exchange. The data is in the form of financial statements that is balance sheets and profit/loss statements taken from the annual financial statements. In this study, the data collection technique which the researcher used has two methods, that is documentation and literature study. The results show that the company's ability to process ROI is stable because the percentage continues to increase every year. The company's ability to return on investment can be said to be quite good. According to the calculation of Residual Income (RI), the result is negative, which means the company has not been able to generate economic added value for shareholders and its financial performance has not been effective and efficient because RI > 0